Tail dependence of financial stocks and CDS markets: Evidence using copula methods and simulation-based inference - Paulo Pereira da Silva; Paulo Tomaz Rebelo; Cristina Afonso (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Using copula methods and simulation-based inference, the authors investigate the association between the performance of a stock index formed by European financial institutions and a basket of CDS contracts of the same sector. Their analysis focuses on (i) assessing the dependence structure of the markets when extreme events occur, and (ii) checking the validity of the conclusion by Merton (On the Pricing of Corporate Debt: The Risk Structure of Interest Rates, 1974) and other similar structural models that there is an intensification of the relationship between stock prices and credit spreads after large negative shocks in the value of firms' assets. The authors show that there is a large tail dependence between the two portfolios. However, the dependence structure seems to be similar with respect to positive and negative innovations in the indexes. Their findings suggest that credit models' implications do not apply to financial firms, likely because the implicit subsidies from governments to financial institutions are distorting the dependency structure.
Keywords: G13; G14; G15; 330; CDS markets; credit risk; Merton's model; copulas; simulation-based inference; banking